Gambaran Distribusi Sudut Eminensia Di Rumah Sakit Gigi Dan Mulut Universitas Trisakti : Kajian pada Pasien Usia 19-21 tahun (Penelitian) - Marcelino I; Carolina Marpaung; Siti Chandra Dwijayanti (Jurnal Kedokteran Gigi Terpadu, 2020)
Mastication system is one of the most important parts of muscoskeletal system. Articular eminence as one component of the mastication system that works as a major component of the temporomandibular-joint (TMJ). The eminence inclination can be classified into 3 groups, flat, normal, and steep. The aim of this research was to assess the distribution view of eminence inclination in patients aged 19-21 years old at Dental Hospital of Trisakti University. This cross-sectional research utilized panoramic imaging in measuring the inclination of the articular eminence. The results of this research indicated that the methods used in the research have differences, whereas the inclination values between age groups have no significant difference. The average eminence inclination value of patient in the age of 19-21 years old still within the 30-60 value range. It can be concluded that the average eminence inclination value of the patient classified to normal category.